Peningkatan kemampuan operasi hitung pembagian melalui media papan hitung pembagian pada siswa kelas IV dan V SDN 28 Tumbang Titi - Veronika Rismayanti; Kezie Tsellamitha Andini Makalew; Elisabeth Tuli Ledun; Johanes Baptis Judha Jiwangga; Sebastianus Widanarto Prijowuntato (Universitas Sanata Dharma, 2026)
This community service activity aimed to improve the division arithmetic operation ability of Grade IV and V students at SDN 28 Tumbang Titi through the use of a Division Counting Board learning medium. The activity involved KKN students as facilitators and was conducted over two meetings during mathematics class hours. The method consisted of three stages: preparation (observation, module development, and media creation), implementation (pre-test, media demonstration, group discussion, and post-test), and monitoring and evaluation. The effectiveness of the program was measured using the Normalized Gain (N-Gain) formula. Results showed that Grade IV achieved an average N-Gain of 58,75 and Grade V achieved 0,40, both falling in the high category. Of 15 total participants, 6,67% were in the high-improvement category, 86,67% in the medium category, and 6,67% in the low category. These findings indicate that the use of concrete manipulative media significantly improved students' understanding of division concepts and can serve as a replicable model for similar community service programs in other schools.